PERAN E-COMMERCE DALAM TRANSFORMASI EKSPOR IMPOR DI ERA DIGITAL - Tamam, Florentya Syifa Hilwah; Putria, Triliunna Meiriska Sari; Wikansari, Rinandita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research examines the role of e-commerce in the transformation of export-import activities in the digital era. E-commerce has revolutionized international trade by facilitating cross-border transactions more efficiently, quickly and cost-effectively. This research uses the Systematic Literature Review (SLR) method to analyze relevant literature from 2020-2023, which discusses various aspects of e-commerce in the context of export-import. The results show that e-commerce provides various benefits, such as increased global market accessibility, logistical efficiency, and transaction transparency. The main factors that support the successful implementation of e-commerce include adequate digital infrastructure, conducive government policies, and service quality that ensures consumer safety and convenience. In addition, e-commerce opens up great opportunities for small and medium-sized enterprises (SMEs) to compete in international markets through direct access to consumers and supply chain optimization. However, the study also found a number of obstacles faced by import-export players in adopting e-commerce. These challenges include limited digital infrastructure, low technological literacy, policies that are not fully supportive, and data security issues. To overcome these obstacles, collaboration between the government and the private sector is needed, including the development of supportive policies, improvement of digital infrastructure, and training for exporters.